2006
DOI: 10.1299/jsmec.49.106
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Wheel Surface Topography in cBN Grinding

Abstract: The wheel surface topography in the grinding process with vitrified cBN wheels has been investigated on the basis of 3-dimensional analysis using a multi-probe SEM, and the relationships between these results and the grinding characteristic parameters have been discussed. Moreover, the change of the wheel surface profile in the grinding process has been evaluated using fractal analysis. There are two regions: an initial wear region and a steadystate wear region, in the grinding process. In the initial wear reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Not only to find out the optimum grinding conditions for various usages, but also to develop a new machining system using cBN grinding wheels, it is essential to clarify the effects of wear behavior of cutting edges on the wheel surface topography (5)~ (7) . In our previous researches, we have reported that the self-sharpening based on the micro fractures takes place in the grinding process with cBN wheels and confirmed that the performance of cBN wheel may be most effectively demonstrated when the generation of such a micro self-sharpening is properly controlled (8), (9) .…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…Not only to find out the optimum grinding conditions for various usages, but also to develop a new machining system using cBN grinding wheels, it is essential to clarify the effects of wear behavior of cutting edges on the wheel surface topography (5)~ (7) . In our previous researches, we have reported that the self-sharpening based on the micro fractures takes place in the grinding process with cBN wheels and confirmed that the performance of cBN wheel may be most effectively demonstrated when the generation of such a micro self-sharpening is properly controlled (8), (9) .…”
Section: Introductionmentioning
confidence: 57%
“…Some fractures occur in initial wear region from stock removal V' w = 0 to 1000 mm 3 /mm and a region from stock Moreover, the number of cutting edges per unit area on the wheel working surface, that is, the cutting edge density C s , was calculated on the basis of 3D-profiles at an area of 2.4 × 1.8 mm 2 observed by 3D-SEM. Detailed calculation method of cutting edge density is shown in our previous paper (8) . The radial distance into the wheel from the outermost protruding cutting point is denoted by radial depth z.…”
Section: Journal Of Advanced Mechanical Design Systems and Manufactmentioning
confidence: 99%
“…The cBN segment detached for the observation can be precisely returned to former state again. It was confirmed experimentally that the cBN wheel with the replaceable cBN segment has almost the same grinding ability as the usual complete cBN wheel (Fujimoto, 2006). The expermental conditions are listed in Table 1.…”
Section: Methodsmentioning
confidence: 68%
“…To clarify the grinding performance of these cBN-U wheels, surface plunge grinding experiments were conducted on a horizontal spindle surface grinding machine. The grinding conditions are listed in Table1. A vitrified cBN wheel with a replaceable cBN insert, as well as a conventional complete grinding wheel, was used to directly observe the changes of the wheel surface in the grinding process (12) . A scanning electron microscope with four electron probes (3D-SEM) was used for 3D observations of the wheel working surface and the grain cutting edges.…”
Section: Cbn Grinding Wheel and Experimental Proceduresmentioning
confidence: 99%